Diabetic Ketoacidosis as an Immune-related Adverse Event from Pembrolizumab in Non–Small Cell Lung Cancer. Issue 6 (July 2017) - Leonardi, Giulia C.; Oxnard, Geoffrey R.; Haas, Andrea; Lang, Joshua P.; Williams, Jonathan S.; Awad, Mark M.
Abstract : Programmed cell death protein 1 pathway inhibitors are now routinely administered to patients with non–small cell lung cancer, and prompt recognition of immune-related adverse events is critical to managing serious drug toxicities. Here, we describe a 66-year-old man with no known history of diabetes who presented with diabetic ketoacidosis after receiving 3 doses of pembrolizumab for lung adenocarcinoma. Autoimmune diabetes is a rare but potentially life-threatening complication of programmed cell death protein 1 inhibitors